Optimalisasi Waktu Proyek Pembangunan Rumah Susun dengan Metode PDM dan PERT - Efrat Ananta; Gunaedy Utomo; Reno Pratiwi (Universitas Batanghari Jambi, 2026)
The construction of the Polda Kaltim apartment building requires systematic time control because the project experienced a delay from the initial contract duration of 240 calendar days. The delay was mainly caused by material distribution constraints, limited workforce availability, and the lack of optimal periodic evaluation between the planned schedule and field realization. This study aims to analyze the critical path and the probability of achieving the evaluated project duration target of 270 calendar days using the Precedence Diagram Method (PDM) and Program Evaluation and Review Technique (PERT). The research data were obtained through literature review, observation, interviews, project documents, and duration-estimation questionnaires completed by 30 respondents. The PDM method was used to identify activity dependencies and critical paths, while the PERT method was applied to calculate expected time, standard deviation, variance, and project completion probability. The results show that the expected project duration is 267 days with a standard deviation of 3.51 days. The evaluated target duration of 270 days has an achievement probability of 80%. In addition, 59 critical activities were used in the PERT variance calculation and require intensive monitoring. Therefore, the integration of PDM and PERT can be used as a scheduling tool to evaluate target-duration achievement, identify critical activities, and formulate more measurable project time-control strategies.